Human Resource Management - Employee motivation at Technology Transfer Center & Environmental Resource Data - Tran, Doan Kien (Khoa Quốc tế, ĐHQGHN, 2019)
Every state or private organization wants to be successful and have desire to get constant progress. The current era is highly competitive and organizations regardless of size, type, technology or market focus are facing employee retention challenges. To overcome these restraints a strong and positive relationship and bonding should be created and maintained between employees and their organizations. Human resource or employees of any organization are the most central part so they need to be influenced and persuaded towards tasks fulfillment. The focus of this study is to analyze the satisfaction on employees’ motivation at DINTE. The study has two sub-objectives; firstly the factors that influent motivation of employees is to be determined. Secondly the relationship of employee motivation and satisfaction is to be examined.